Comparative Study on Properties of Polylactic Acid Nanocomposites with Cellulose and Chitin Nanofibers Extracted from Different Raw Materials. (20th November 2017) - Li, Jingjing; Li, Jian; Feng, Dejun; Zhao, Jingfeng; Sun, Jingrong; Li, Dagang
Abstract : Polylactic acid (PLA) was reinforced with ultralong cellulose and chitin nanofibers extracted from four raw materials by extrusion. The mechanical, rheological, thermal, and viscoelastic performances of four nanocomposites were comparatively studied in detail. The results showed that fibrillation of poplar was much easier than that of cotton, and fibrillation of crab shell was relatively hard as compared to prawn shell. The poplar CNFs/PLA composite exhibited the best mechanical properties among four nanocomposites due to the highest aspect ratio of nanofibers, while both the cotton CNFs/PLA composite and the crab shell CHNFs/PLA composite had low mechanical strength due to the relatively low aspect ratio. FE-SEM images showed that the ultralong nanofibers were uniformly dispersed in PLA matrix for all four samples with the water preblending method. The CTE values of the nanocomposites with 40 wt% nanofibers extracted from poplar, cotton, crab shell, and prawn shell were 69.5 × 10 −6 K −1, 79.6 × 10 −6 K −1, 77.2 × 10 −6 K −1, and 75.3 × 10 −6 K −1, respectively. All the results indicated that the aspect ratio of the nanofibers has a great influence on the performance of the composites, irrespective of the composites prepared by cellulose or chitin.